Edukasi Tentang Peran Media Sosial Dalam Meningkatkan Pendapatan Pada Home Industry - Ayudho Selviani; Rossa Ayuni; Ade Irma Suryani (Almaun: Jurnal Pengabdian Kepada Masyarakat, 2023)
The need for fast information is currently increasingly needed along with the increasingly rapid development of information technology. This is a driving factor for the public or agencies to utilize information technology. Don't forget the people involved in Home Industry activities. Home Industry (Household Industry) is a home product business or also a small company. It is said to be a small company because this type of economic activity is centered at home. Home industry is able to expand employment opportunities and provide broad economic services to the community, it can play a role in improving the community's economy and family income, reducing unemployment and improving community welfare. One way to maximize the role of Home Industry activities. Home Industry is providing education to the public regarding the use of social media.